GAMBARAN PENGETAHUAN PERAWAT TENTANG ASUHAN KEPERAWATAN HIPERBILIRUBINEMIA NEONATUS DI RUANG PERINATOLOGI : Studi Literature - Juliant Immanuel Harley Davika Ginting, (2020)
Providing nursing services to neonates is certainly different, given the baby's ability to overcome problems is still in a different maturity process compared to adults. The role of the nurse is very important in taking care of the baby in order to avoid the failure of intervention in handling the baby. The results of research conducted by several experts show that the intervention carried out by several nurses has side effects, not only that there are some interventions that are not widely applied in the management of neonates with hyperbilirubin. This review literature aims to know systematically about the description of nurses' knowledge about nursing care for hyperbilirubinemia in the perinatology room: Literature Study. Literature Review is carried out by using database searches such as Google Scholar and PubMed. The keywords used for this search are "Nurse Knowledge", "NICU nurses", "Hyperbilirubinemia Nursing Care" and "Neonator jaundice". With the criteria of Indonesian or English language journals, based on 2015-2020 with full text journals. The results obtained and used in this literature review are 13 journals. Knowledge Description Nurses have a relationship in handling infants with hyperbilirubin. Age factors, recent education, and work experience that influence nurses in taking nursing care. Nurses' knowledge is very important for nursing neonatal hyperbilirubinemia care in the NICU room and perinatology. The advice given is that nurses' knowledge is also expected to be improved in analyzing and handling infants with hyperbilirubin, so that the next step nurses can consider interventions given to infants with neonatal hyperbilirubin.